Long-term wage inequality in imperial China: From 202 BCE to 1912 CE - Qiang Wu; Guangyu Tong; Peng Zhou (Cardiff University, Cardiff Business School, 2024)
This paper attempts to describe and explain the long-term evolution of wage inequality in imperial China, covering over two millennia from the Han dynasty to the Qing dynasty (202 BCE-1912 CE). Based on historical government records of official salaries, commodity prices, and agricultural productivity, we convert various forms of salaries to equivalent rice volumes and comparable salary benchmarks. Wage inequality is measured by salary ratios and (partial) Gini coefficients between official and peasant classes as well as within the official class. The inter-class wage inequality features an "inverted U-u" pattern-first rose before the Tang dynasty and then declined afterwards (the "inverted U" trends) with "inverted u" dynastic cycles. The intra-class wage inequality has a secular decline trend. We propose a unified framework incorporating technological, institutional, political, and social (TIPS) mechanisms to explain both long-term and short-term patterns. It is concluded that the technological mechanism dominated the rise of wage inequality, while the political mechanism (emperor-bureaucracy power tensions) drove the decline.
Keywords: 330